2003
DOI: 10.1038/sj.onc.1206300
|View full text |Cite
|
Sign up to set email alerts
|

Novel succinate dehydrogenase subunit B (SDHB) mutations in familial phaeochromocytomas and paragangliomas, but an absence of somatic SDHB mutations in sporadic phaeochromocytomas

Abstract: Phaeochromocytomas arising in adrenal or extra-adrenal sites and paragangliomas of the head and neck, in particular of the carotid bodies, occur sporadically and also in a familial setting. In addition to mutations in RET and VHL in familial disease, germline mutations in SDHD and SDHB genes that encode subunits of mitochondrial complex II have also been associated with the development of familial phaeochromocytomas. To further investigate the role of SDHD and SDHB in the development of these tumours we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 26 publications
5
60
0
1
Order By: Relevance
“…In particular, loss of chromosome 1p is important for both MEN 2-related and sporadic tumors but not the VHL-related pheochromocytomas. These ®ndings are consistent with a recent report by Benn et al (2000), who found loss of 1p in 61% of sporadic pheochromocytomas and 80% of MEN2-related pheochromocytomas but none of the two VHL-related pheochromocyotmas. It will be interesting to conduct a large study to correlate the clinical parameters of these various types of pheochromocytomas with these genetic alterations.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, loss of chromosome 1p is important for both MEN 2-related and sporadic tumors but not the VHL-related pheochromocytomas. These ®ndings are consistent with a recent report by Benn et al (2000), who found loss of 1p in 61% of sporadic pheochromocytomas and 80% of MEN2-related pheochromocytomas but none of the two VHL-related pheochromocyotmas. It will be interesting to conduct a large study to correlate the clinical parameters of these various types of pheochromocytomas with these genetic alterations.…”
Section: Discussionsupporting
confidence: 82%
“…Using DGGE and sequencing, we detected seven different germline nucleic acid changes. The intronic sequence variants ivs2+33A>G and ivs2+35G>A are known polymorphisms (Benn et al 2003) with a reported allelic frequency of 4% and 12% respectively (Benn et al 2003). We detected an almost identical frequency of these polymorphisms in sporadic and familial MTC patients as well as in our control individuals (Table 2).…”
Section: Discussionsupporting
confidence: 60%
“…16 In contrast, both maternal and paternal inheritance of SDHB mutations has been reported. 17 The mutation in the SDHB gene reported for our patient,724C4T (Arg242Cys), has been previously reported for a female patient with a unilateral glomus vagale tumour and no family history, but the pathogenicity of this mutation has not yet been established. 18 It is possible that this variant could be a normal polymorphism of the gene, although subunits SDHA and SDHB of succinate dehydrogenase (mitochondrial complex II) form the hydrophilic catalytic part of the complex and are highly conserved.…”
Section: Discussionmentioning
confidence: 99%